Circulating Endothelial Progenitor Cells Present an Inflammatory Phenotype and Function in Patients With Alcoholic Liver Cirrhosis - Kaur, Savneet; Sehgal, Rashi; Shastry, Saggere M.; McCaughan, Geoffrey; McGuire, Helen M.; Fazekas St de Groth, Barbara; Sarin, Shiv; Trehanpati, Nirupma; Seth, Devanshi (Frontiers in Physiology, 2018)
Background and Aim: Endothelial progenitor cells (EPCs) have been implicated in liver injury and repair. However, the phenotype and potential of these heterogenous EPCs remain elusive. In particular, their involvement in the pathogenesis of alcoholic liver cirrhosis (ALC) remains unclear. The current study extensively characterized the phenotype and functions of EPCs to understand their role in ALC pathogenesis. Methods: Circulating EPCs were identified as CD34+CD133+CD31+ cells by flow cytometer in ALC patients (n=7) and healthy controls (HC, n=7). A comprehensive characterization of circulating EPCs using more than 30 phenotype markers was performed by mass cytometer time of flight (CyTOF) in an independent cohort of age and gender matched ALC patients (n=4) and controls (n=5). Ex vivo cultures of circulating EPCs from ALC patients (n=20) and controls (n=18) were also tested for their functions, including colony formation, LDL uptake, lectin binding and cytokine secretion (ELISA). Results: Three distinct populations of circulating EPCs (CD34+CD133+CD31+) were identified, classified on their CD45 expression (negative: CD45-; intermediate: CD45int; high: CD45hi). CD45int and CD45hi EPCs significantly increased in ALC patients compared to controls (p-val 0.006). CyTOF data showed that CD45hi EPCs were distinct from CD45- and CD45int EPCs, with higher expression of T cell and myeloid markers, including CD3, CD4, HLA-DR, and chemokine receptors, CCR2, CCR5, CCR7 and CX3CR1. Similar to circulating EPCs, percentage of CD45hiCD34+CD31+ EPCs in ex-vivo cultures from patients, were significantly higher compared to controls (p <0.05). Cultured EPCs from patients also showed increased LDL uptake, lectin binding and release of TNF-alpha, RANTES, FGF-2 and VEGF. Conclusions: We report the first extensive characterization of circulating human EPCs with distinct EPC subtypes. Increase in CD45hi EPC subtype in ALC patients with enhanced functions, inflammatory cytokines and angiogenic mediators in patients suggests an inflammatory role for these cells in ALC.